Biomoléculas extraídas por sbas: Ejemplos prácticos - Dutra-Molino, J. V.; Araujo Feitosa, V.; de Lencastre-Novaes, L. C.; de Carvalho Santos-Ebinuma, V. [UNESP]; Moreni Lopes, A.; Faustino Jozala, A.; de Aráujo Viana Marques, D.; Pellegrini Malpiedi, L.; Pessoa, A. (My University, 2014)
The actual biotechnology industry demands fast and economic upstream and downstream processes to purify biomolecules. In this context, different purification techniques, that offer both high recovery and purity to the final product, have been assayed by different research groups. Liquid-liquid extraction with aqueous two-phase systems is one of the most studied methodologies for bio-separation. This technique presents several advantages such as mild conditions of working, cost-effectiveness, short-time consumption and high recovery percentage of the final product. With the aim to present a comparison of liquid-liquid extractions with other techniques, several aqueous two-phase extraction processes of biomolecules are presented in this review. We presented the advantages and disadvantages of them as of the compared systems. In general, the highest final product purities are achieved when different methodologies are combine, being the chromatographic ones the most applied in the last stages for the high purification factor obtained after them. Alternative methodologies, such as aqueous two-phase systems (ATPS), i.e., PEG/salts or ionic liquids; aqueous two-phase micellar systems, using solvents and surfactants; and extractive fermentation with ATPS, are relevant for both cost-effectiveness and time-saving of the purification process.
Biomolecules extracted by ATPS: Practical examples
Keywords: Biomolecules; Downstream processing; Liquid-liquid extraction; Polymers; Surfactant